2021
DOI: 10.1097/md.0000000000026035
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of acne increasing suicide risk

Abstract: Acne is associated with depression and anxiety; however, the relationship between acne and suicide is still unclear. This study is aimed to evaluate the association between acne and suicide by conducting a meta-analysis. Studies were identified by electronic searches of the PubMed and EMBASE databases from their inception through Jan 10, 2020. Two authors separately assessed the quality and extracted data from the selected studies. When the heterogeneity was significant, we used a random-effects model to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…12 In a recent meta-analysis including 2,276,798 participants across 5 separate studies, researchers found that suicide was positively associated with acne, carrying an odds ratio of 1.50 (95% CI, 1.09-2.06). 13 Rosacea-Rosacea is a common chronic inflammatory skin disease characterized by facial erythema, telangiectasia, phymatous changes, papules, pustules, and ocular irritation. The estimated worldwide prevalence is 5.5%.…”
Section: Resources For Suicide Preventionmentioning
confidence: 99%
“…12 In a recent meta-analysis including 2,276,798 participants across 5 separate studies, researchers found that suicide was positively associated with acne, carrying an odds ratio of 1.50 (95% CI, 1.09-2.06). 13 Rosacea-Rosacea is a common chronic inflammatory skin disease characterized by facial erythema, telangiectasia, phymatous changes, papules, pustules, and ocular irritation. The estimated worldwide prevalence is 5.5%.…”
Section: Resources For Suicide Preventionmentioning
confidence: 99%
“… 70 Adolescents and young adults with acne have increased association with suicide (either ideation, attempt, or death). 71 Concerns about perceived adverse effects, effectiveness of acne treatments, and perceived medical provider trivialization exacerbate psychological impact. 72 …”
Section: Mental Health Among Acne Patients and In Transgender Adolesc...mentioning
confidence: 99%
“…70 Adolescents and young adults with acne have increased association with suicide (either ideation, attempt, or death). 71 Concerns about perceived adverse effects, effectiveness of acne treatments, and perceived medical provider trivialization exacerbate psychological impact. 72 Few studies linking acne with adverse mental health outcomes focus on transgender and gender non-conforming adolescents, despite their disproportionate mental health burden.…”
Section: Mental Health Among Acne Patients and In Transgender Adolesc...mentioning
confidence: 99%
“…Thirty-five (35) volunteers recruited by the study site signed the informed consent document and complied with the inclusion and exclusion criteria. No volunteers withdrew or were excluded from the study.…”
Section: Assessment Of the Acnegenic And Comedogenic Potential And Sk...mentioning
confidence: 99%